"Schetynówką" do "jaroszewiczówki" na "Palikotówkę" za "kuroniówkę". Rzeczowniki z sufiksem -ówka motywowane nazwiskami polityków = "Schetynówką" do "jaroszewiczówki" na "Palikotówkę" za "kuroniówkę". Nouns with the suffix -ówka motivated by the names of politicians - Dawidziak-Kładoczna, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In this article, I deal with derivatives created with the suffix -ówka, motivated by the name of a politician. In total, I collected 53 such units. They were confirmed in 86 meanings. They represent various categories, including names of the roads ("gierkówka", "schetynówka"), villas ("cyrankiewiczówka", "jaroszewiczówka"), financial amounts ("wałęsówka", "religówka"), alcoholic beverages ("Palikotówka", "Misiewiczówka") and names of weapons ("batorówka", "kościuszkówka").
Keywords: słowotwórstwo; derywaty odnazewnicze; konotacje; nazwiska polityków; word-formation; derivatives from surnames; connotations; names of politicians